2022
DOI: 10.1093/rheumatology/keac140
|View full text |Cite
|
Sign up to set email alerts
|

Humoral response and safety of BNT162b2 mRNA vaccine in children with rheumatic diseases

Abstract: Objectives The vaccine represents a cornerstone in tackling the COVID-19 pandemic and with the approval of the BNT162b2 mRNA vaccine in December 2020, it has become a beacon of hope for people around the world, including children. This study aimed to present the data on the humoral response and safety of vaccine in a cohort of patients with pediatric rheumatic diseases (PedRD) receiving immunomodulatory treatments. Methods Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Of the 88 articles included, there were 12 RCTs, two non-randomized clinical trials, 40 cohort studies, 19 cross-sectional studies, and 15 case‒control studies. In the studies included, 16 articles were available for immunogenicity analysis (Supplementary Table 2) [ 14 , 15 , 18 , 31 43 ]; 38 articles were available for effectiveness analysis (Supplementary Table 3) [ 14 , 17 , 19 , 31 , 44 77 ]; and 49 articles were available for safety analysis (Supplementary Table 4) [ 14 16 , 18 , 20 24 , 31 , 34 , 35 , 37 , 41 , 43 , 45 , 47 , 50 , 55 , 78 107 ]. Children and adolescents are involved in 27 countries, including the United States, China, Australia, Argentina, Italy, Israel, France, Denmark, and South Korea, which have larger cohorts (> 100,000 people).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 88 articles included, there were 12 RCTs, two non-randomized clinical trials, 40 cohort studies, 19 cross-sectional studies, and 15 case‒control studies. In the studies included, 16 articles were available for immunogenicity analysis (Supplementary Table 2) [ 14 , 15 , 18 , 31 43 ]; 38 articles were available for effectiveness analysis (Supplementary Table 3) [ 14 , 17 , 19 , 31 , 44 77 ]; and 49 articles were available for safety analysis (Supplementary Table 4) [ 14 16 , 18 , 20 24 , 31 , 34 , 35 , 37 , 41 , 43 , 45 , 47 , 50 , 55 , 78 107 ]. Children and adolescents are involved in 27 countries, including the United States, China, Australia, Argentina, Italy, Israel, France, Denmark, and South Korea, which have larger cohorts (> 100,000 people).…”
Section: Resultsmentioning
confidence: 99%
“…Rheumatic disorders were studied in four studies, and type 1 diabetes, Down syndrome, solid tumor, neurodisability, and cystic fibrosis were studied in one each. Eight studies (Akgün 2022; Dimopoulou 2022; Heshin-Bekenstein 2022; King 2022; Michos 2022; Piccini 2022; Riviere 2021; Valentini 2022)[3,4,810,2224] employed a cohort design, whereas one used a cross-sectional design(Haslak 2022)[6]. Most investigations were undertaken in Europe ( Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of RoB for these studies was conducted using ROBINS-I (Supplementary Table 3). Six studies had an unclear overall risk of bias (Akgün 2022…”
Section: Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of disease flare was 4.4% after the second mRNA vaccine dose ( 64 ). A study that examined the BNT162b2 mRNA vaccine in 41 adolescents with AIIRD reported that patients who received immunomodulatory treatments safely achieved an effective humoral response after two-dose regimen vaccine, without interrupting their current treatments ( 65 ). A 2022 publication reported a good safety profile in a cohort of 228 children aged 12–18 years ( 66 ).…”
Section: Covid-19 and Vaccination What Is Already Knownmentioning
confidence: 99%